2018
DOI: 10.1124/mol.118.111914
|View full text |Cite
|
Sign up to set email alerts
|

Transmembrane Domain 1 of Human Organic Anion Transporting Polypeptide 2B1 Is Essential for Transporter Function and Stability

Abstract: Organic anion transporting polypeptides (OATPs, gene symbol ) are important membrane transporter proteins that mediate the uptake of wide ranges of endogenous and exogenous compounds. OATP2B1 has been found in multiple organs and tissues, including the liver, small intestine, kidney, brain, placenta, heart, skin, as well as skeletal muscle, and is proposed to be involved in the uptake of orally administered drugs. Quite a few reports have demonstrated that transmembrane domains (TMs) are crucial for proper fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 36 publications
4
7
0
Order By: Relevance
“…Whereas the carbonyl oxygen at position R-17 position typically forms the H-bond interaction with the GLN196 side chain, H-bond formation between the phosphono group at either R-2 or R-4 position is typically formed with SER66 (or sometimes also with the neighboring GLN62; see Figures and S14). SER66 was reported in literature to be important for transport of endogenous substrates, and it is interesting that this residue is located at the corresponding position 45 in OATP1B1 and OATP1B3 (which seems to be important for differences in binding in these other two transporters; see previous chapter). Also, GLN62 is an experimentally confirmed functionally important residue in OATP2B1 …”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Whereas the carbonyl oxygen at position R-17 position typically forms the H-bond interaction with the GLN196 side chain, H-bond formation between the phosphono group at either R-2 or R-4 position is typically formed with SER66 (or sometimes also with the neighboring GLN62; see Figures and S14). SER66 was reported in literature to be important for transport of endogenous substrates, and it is interesting that this residue is located at the corresponding position 45 in OATP1B1 and OATP1B3 (which seems to be important for differences in binding in these other two transporters; see previous chapter). Also, GLN62 is an experimentally confirmed functionally important residue in OATP2B1 …”
Section: Resultsmentioning
confidence: 95%
“…SER66 was reported in literature to be important for transport of endogenous substrates, and it is interesting that this residue is located at the corresponding position 45 in OATP1B1 and OATP1B3 (which seems to be important for differences in binding in these other two transporters; see previous chapter). Also, GLN62 is an experimentally confirmed functionally important residue in OATP2B1 …”
Section: Resultsmentioning
confidence: 95%
“…A recent study showed that TM1 is important for maintaining proper function of OATP2B1 . However, no study examining the role of TM1 for the function of OATP1B3 has been reported thus far.…”
Section: Resultsmentioning
confidence: 99%
“…Several groups have strived to identify the substrate-interacting residues and delineate the transport translocation mechanism of OATPs. However, most of these studies focused on transporters other than OATP1C1 or substrates other than iodothyronines (282)(283)(284)(285)(286)(287)(288)(289)(290)(291)(292)(293)(294). Therefore, it is unclear to what extent these findings also apply to the transport of iodothyronines.…”
Section: Structure Function Relationship Of Organic Anion Transporting Polypeptidesmentioning
confidence: 99%